Cost-effectiveness of an intervention to improve the quality of nursing care among immobile patients with stroke in China: A multicenter study. (October 2020) - Liu, Hongpeng; Zhu, Dawei; Song, Baoyun; Jin, Jingfen; Liu, Yilan; Wen, Xianxiu; Cheng, Shouzhen; Nicholas, Stephen; Wu, Xinjuan
Abstract: Background: While a nursing intervention program for immobile patients with stroke can improve clinic outcomes, less is known about the cost-effectiveness of these interventions. Objectives: The goal of this study was to evaluate the cost-effectiveness of the intervention program for immobile patients with stroke in China. Design: A cost-effectiveness analysis alongside a pre-test/post-test (before and after) study was undertaken from a health care perspective. Settings: Participants were recruited from 25 hospitals among six provinces or municipal cities in eastern (Guangdong province, Zhejiang province, and Beijing municipal city), western (Sichuan province), and central (Henan province and Hubei province) China. Participants: A total of 7, 653 immobile stroke patients were included in our sample. Patients in routine care settings were recruited from November 2015 to June 2016, and the recruitment of the intervention group patients was from November 2016 to July 2017. Methods: To adjust for potential bias from confounding variables, the 1:1 propensity score matching yielded matched pairs of 2, 966 patients in the routine care group and 2, 966 patients in the intervention group, with no significant differences in sociodemographic or clinical characteristics between two groups. All patients were followed-up 3 months after enrolment in the study. Total healthcare costs were extracted from the hospital information system, with the health outcome effectiveness of the intervention program measured using the EuroQol five-dimensional questionnaire (EQ-5D) instrument and the cost-effectiveness of the intervention measured by the incremental cost-effectiveness ratio with a time horizon of 3 months. Results: Compared to routine care, the intervention program decreased the total costs of stroke patients by CN¥4, 600 (95% confidence interval [CI]: [-7050, -2151]), while increasing quality-adjusted life year 0.009 (95% CI: [0.005, 0.013]). The incremental cost-effectiveness ratios over 3 months was CN¥–517, 011 per quality-adjusted life year (95% CI: [-1, 111, 442, -203, 912]). Subgroup analysis reveals that both the health-related quality of life and cost effectiveness improved significantly for ischemic patients and tertiary hospitals patients while for hemorrhagic patients and non-tertiary hospital patients only the health-related quality of life improved significantly. Conclusions: Findings from this first cost-effectiveness analysis in immobile stroke patients provide evidence that an intervention program provided significant cost saving, but mainly in ischemic patients and tertiary hospital patients. Wider adoption of such programs may be a sensible approach to reducing the burden of stroke and for immobile patients more generally.